2020
DOI: 10.1021/acs.molpharmaceut.0c01091
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Derivative of Hydrocortisone as Glucocorticoid Receptor-Targeted Nanotherapeutics for Synergistic, Combination Therapy against Colorectal Tumor

Abstract: Hydrocortisone, a natural glucocorticoid secreted by adrenal and extra-adrenal tissues, locally governs the transcription of genes involved in inflammation, immune response, metabolism, and energy homeostasis via binding to its cognate glucocorticoid receptor (GR). In this study, we show that modified hydrocortisone (HC16), a cancer-selective cytotoxic molecule, showed synergism in combination with drugs like Doxorubicin and docetaxel, self-assembled into vesicles, entrapped docetaxel and complexed with anti-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…While exploring the reason for the selective killing of cancer cells, a nanoaggregate-forming ability of these derivatives was noted. It was interesting because self-aggregating properties have been shown by us in cationic lipid conjugates of other small molecules and among natural steroids, hydrocortisone, before this study. However, we are the first to report herein that another natural steroid hormone, progesterone, in its cationic lipid-conjugated derivatives, also exhibits similar self-aggregating properties. Presented herein are the details on the studies performed on the most potent derivative, i.e., PR10 nanoaggregates, and the mechanism involved in its cancer cell-selective uptake that led to its potent anticancer activity.…”
Section: Introductionmentioning
confidence: 76%
“…While exploring the reason for the selective killing of cancer cells, a nanoaggregate-forming ability of these derivatives was noted. It was interesting because self-aggregating properties have been shown by us in cationic lipid conjugates of other small molecules and among natural steroids, hydrocortisone, before this study. However, we are the first to report herein that another natural steroid hormone, progesterone, in its cationic lipid-conjugated derivatives, also exhibits similar self-aggregating properties. Presented herein are the details on the studies performed on the most potent derivative, i.e., PR10 nanoaggregates, and the mechanism involved in its cancer cell-selective uptake that led to its potent anticancer activity.…”
Section: Introductionmentioning
confidence: 76%
“…A unique approach could thus be to access an alternate pathway by targeting GR, thus achieving efficient antitumor effect in CT26 colon tumor model using ESC8 and Dex-associated nanoformulation (Jinka et al, 2021). Same effect was also shown using hydrocortisone (a GR hormone)-conjugated cationic lipid based unique self-aggregated formulation (Sridharan et al, 2021). Tailored small molecules designed against custom mutant profiles if combined with such SHRtargeted therapeutic approaches might result in overall improved outcomes in terms of patient survival, even for cancers possessing gene mutations in future.…”
Section: Mutations In Genetic Profiles and Their Targeted Therapymentioning
confidence: 96%
“…SAR study indicated HYC16, the aliphatic 16 carbon chain based cationic lipid-modified hydrocortisone, to be the most potent and selective in killing cancer cells and potently inhibiting angiogenesis (Rathore et al, 2016). As shown by other cationic lipid-modified GCs, for example, DX10, the same molecule HYC16 also exhibits potent drug sensitizing ability in cancer cells through reversal of EMT (Sridharan et al, 2021). Innovatively, HYC16 also exhibits a unique self-aggregating property, which is described in details later under Section 5.1.4, thus suggesting the advent of novel class of nanotherapeutics derived from steroid hormone.…”
Section: Dermatological Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 HC is a synthetic and naturally occurring glucocorticoid, which has anti-inflammatory, immunosuppressive, anti-allergic, and anti-shock effects. 11 17α-Hydoxyprogesterone (OHP) is a derivative of progesterone transformed by 17α-hydroxylase. Overuse has caused the accumulation of steroid hormones in animals, which disturbs the human endocrine system via the food chain.…”
Section: Introductionmentioning
confidence: 99%